Novel research methods on evaluating the nexus between environment and energy use: evaluating the role of tourism in the pre-COVID period. Issue 1 (31st December 2023) - Niu, Junyi
Abstract: Since the fossil fuels are the principal energy sources across the globe, it is considered as the major reason for environmental degradation. Although, the fossil fuel consumption contributes to maintain industrial production, which is a key factor of economic growth, yet tourism is also among the key sources of revenue for China in the pre-Covid-19 pandemic. However, after the emergence of this novel pandemic, both fossil fuel consumption and tourism are severely affected that slowdowns China's economic progress and could have influence on environmental quality. This study investigates the impact of traditional fossil fuel, economic growth, and tourism on carbon emissions level in China over the period 1995–2020. Using time series estimating approaches, all the variables are found stationary at first difference. Due to irregular distribution of data, this study employed the novel Quantile-on-Quantile regression. The estimated results reveal that consumption of fossil fuel significantly enhances the level of carbon emissions in China. Whereas the impact of economic growth and tourism on carbon emission is mixed. The influence of both the variables is found positive in the lower and medium quantiles, while negative in the upper quantiles. This study also employed the pairwise Granger causality test, that validates two-way causal nexus between fossil fuel consumption—carbon emission and economic growth—carbon emissions. While one way causality from tourism to carbon emissions is evident in the empirical results. This study suggests lowering of fossil fuel consumption by using the alternative energy sources and increase tourism stringent environmental regulations for environmentally destructive tourism activities.